Reaction Pathways and Mechanisms in Thermocatalytic Biomass Conversion II : Homogeneously Catalyzed Transformations, Acrylics from Biomass, Theoretical Aspects, Lignin Valorization and Pyrolysis Pathways /: Homogeneously Catalyzed Transformations, Acrylics from Biomass, Theoretical Aspects, Lignin Valorization and Pyrolysis Pathways. (2015) - Unknown
No abstract available